Soybean cultivars in southeast region of Rio Grande do Sul State, Brazil - Vernetti, Francisco de Jesus; Gastal, Mario Franklin da C.; Zonta, Elio Paulo; Raupp, Antonio André Amaral (Pesquisa Agropecuaria Brasileira, 2014)
The yield performance of soybean (Glycine max (L.) Merrill) cultivars, in three counties of the Southeast of Rio Grande do Sul, Brazil, was evaluated along twelve crop seasons (1971-1983). Thirty five field trials, in randomized blocks design, were planted in three soil types that predominate in the region. Twenty three cultivars recommended for planting in that State were evaluated: eight early (V-VI), five medium (VII), six semi-late (VIII) and four late (VIII). The combined analysis of variance of the experiments grouped according to soil type and/or county (ies) showed the superior yielding performance of the cultivars Planalto, Pérola and IAS 5 (early), Bragg and IAS 4 (medium) and Hampton (semilate), as well as the poor yielding of Hardee and Santa Rosa (late), Bossier (semi-late), Paraná and Prata (early). In another paper the phenotypic stability of the cultivars will be presented.
Keywords: Glycine max; cultivars